PERSEPSI GURU TENTANG KEPEMIMPINAN KEPALA MADRASAH SERTA PENGARUHNYA DALAM MENINGKATKAN KOMPETENSI PAEDAGOGIK GURU - Agus Salim; Muhtadi; Atim (Arsy : Jurnal Studi Islam, 2017)
Principal has the authority to function as a leader in command and control of teachers who are under his leadership. The function of principal leadership and its influence on the pedagogical competence of teachers expected more highly skilled, focused and professional , making it easier to capture , ingest and realize later in the day to day tasks.Design of this research is a quantitative research because testing the influence between two variable there is independent variable (leadership) and dependent variable (Paedagogical Competence). Collecting data methods using questionnaire which is given to all the teachers in Islamic Yunior High School of Saradan Madiun as the respondents than it is analyzed through a simple linear regression analysis using SPSS software version 17.Based on the hypothesis test found the conclusion that (1) Ha accepted or there is a significant influence on the school leadership on teachers profesionalism in Islamic Yunior High School of SaradanMadiun with a probability level of 0.000 (p < 0.01) and accounted for 97,6% (2) regression coefficient of 0.335 means that any increase in the school leadership will be followed by an increase in teachers pedagogical professionalism Islamic Yunior High School of Saradan Madiun through regression equation : Y = -11.140 + 0.335 X.